Surface Nanocoating with Plant‐Derived Pectins Improves Fibroblast Response In Vitro. (7th October 2018) - Folkert, Justyna; Mieszkowska, Anna; Gaber, Timo; Miksch, Korneliusz; Dirscherl, Kai; Gurzawska, Katarzyna
Abstract : Pectins, plant‐derived polysaccharides, are novel candidates for biomaterial nanocoatings. Their chemical structure imitates the polysaccharides from the extracellular matrix of mammals, providing bio‐specific cell adhesion. It is possible to control the structure of pectin rhamnogalacturonan‐I (RG‐I) by enzymatic modification. RG‐Is has been proposed for surface nanocoating of orthopedic and dental titanium implants due to its effect on osseointegration with stimulation of bone and connective tissue healing. The aim of the current study is to evaluate in vitro, the impact of plant‐derived pectin RG‐I nanocoating on the cellular response of human fibroblasts. In this study, unmodified RG‐I and enzymatically modified RG‐I with low amount of arabinose and high amount of galactose are examined. All in vitro studies are performed on tissue culture polystyrene plates, whose surfaces are coated with unmodified and modified RG‐I. The results show that the nanocoating with pectin RG‐Is increas proliferation, cell metabolic activity, and gene expression of COL1A1, FN1, FGFR1, BMP7, and MMP2 as compared to control surface, without pectin coatings. The results show that nanocoating with RG‐Is has the capacity to improve fibroblast proliferation, differentiation, and extracellular matrix protein production, and may therefore be considered as a potential candidate for further improvement of bone and connective tissue regeneration. Abstract : Rhamnogalacturonan‐Is (RG‐Is), plant‐derived polysaccharides, are potential candidates for surface nanocoating of medical devices, due to their effect on osseointegration, stimulating bone and connective tissue healing. Nanocoating with RG‐Is, promote gingival fibroblast proliferation, metabolic activity and expression of genes that reflect the turnover of the extracellular matrix.